DETERMINANTS OF POVERTY FEMALE HEAD OF HOUSEHOLD IN THE PROVINCE OF BANGKA BELITUNG ISLAND - Rahma Nurhamidah (International Conference on Social and Islamic Studies, 2021)
The change in the role of women due to the Covid-19 pandemic make women have a role in supporting the family economy. Women are forced to take over the leadership of the household, althought their position as the head of the household is classified as socially and economically vulnerable. This study aims to analyze the determinants of poverty experienced by female household heads based on data from the March 2020 Susenas. The condition of Bangka Belitung which is dominated by women with the opportunity for women to achieve development goals that are smaller than men, make women to be more vulnerable to poverty. Bangka Belitung was recorded as the province with the highest wage increase in August 2020 with an increase of 8.54 percent. However, the much lower national average wage for female workers provides opportunities for women to live in poverty, especially women who act as heads of households. The results showed that the determinants of poverty for female household heads in the Province of the Bangka Belitung Islands were marital status, employment status and the number of dependents in the household. Regional Government of the Province of Kep. Bangka Belitung needs to make efforts to reduce the poverty level of households with female household heads, including by campaigning for birth control and business skills guidance and marketing platforms for household heads whose work is in the informal sector.